OP0051 Relationship Between Physical Activity and Hip Pain in Persons with and Without Femoroacetabular Impingement: A Population-Based Case-Control Study. (9th June 2015) - Kopec, J.A.; Li, L.C.; Zhang, C.; Barber, M.; Qian, H.; Wong, H.; Prlic, H.; Ratzlaff, C.; Cibere, J.; Sayre, E.C.; Ye, J.; Forster, B.; et al.
Abstract : Background: Femoroacetabular impingement (FAI) and physical activity involving hip flexion have been suggested as key risk factors for hip pain among young and middle-aged individuals [1] but population studies have been lacking. Objectives: To determine if physical activity involving hip flexion is a risk factor for persistent or recurrent hip pain in young and middle-aged persons with and without FAI. Methods: A population sample of persons aged 20-49 with (cases) and without (controls) hip pain in Metro Vancouver, Canada, was selected through random digit dialing. Hip pain was defined as pain in the groin or upper thigh in the past 12 months that lasted 6 weeks or longer or occurred on 3 or more occasions. Subjects completed a lifetime physical activity questionnaire including domestic, occupational and sports/recreational activities. Flexion scores were calculated from reported total hours of activities involving hip flexion>70 degrees (e.g., squatting, kneeling, skiing, rowing, but excluding sitting). Data on peak hip flexion for various activities were derived from the literature. Standardized X-rays of the pelvis/hips with AP and Dunn views were obtained. FAI was defined as one or more of the following: lateral centre edge angle (LCE) >40°, alpha angle >55° and positive cross-over sign. We analyzed the relationship between flexion scores and hip pain among persons with and without FAI using logistic regression. In secondary analyses we a) used hip (rather than person) as the unit of analysis; b) considered only activities prior to the onset of pain. Odds ratios (OR) are reported for a one standard deviation difference in flexion scores. Results: Data were obtained for 500 subjects, 269 cases and 231 controls. Mean age was 43 years in both groups, 34% of the cases and 39% of the controls were male. Prevalence of radiographic FAI was 49% in the cases and 43% in the controls. Mean (SD, range) flexion scores were 78 (126, 0-1074) in the cases and 60 (112, 0-782) in the controls for work/domestic activities, and 25 (37, 0-198) and 24 (48, 0-306) for sports activities, respectively. After adjusting for age and sex, a higher flexion score for work/domestic activities was associated with hip pain in subjects with FAI (OR=1.54, 1.01-2.35) but not in those without FAI (OR=1.10, 0.89-1.36). For sports/recreational activities, flexion score was not significantly associated with pain in either group (OR=0.90, 0.71-1.14 and OR=1.25, 0.93-1.68 for those with and without FAI, respectively). The hip-based analysis and the analysis limited to activities prior to the onset of pain showed similar results. Conclusions: A one SD increase in the frequency of domestic and work-related activities involving hip flexion is associated with a 50% increase in the risk of persistent or recurrent hip pain in young and middle-aged persons with radiographic FAI. This finding may help understand the causes of hip osteoarthritis. References: Leunig M, Ganz R. Femoroacetabular impingement. A common cause of hip complaints leading to arthrosis. Unfallchirurg. 2005;108(1):9-10, 12-7. Acknowledgements: The study was supported by a grant from the Canadian Institutes of Health Research. Disclosure of Interest: None declared